An Integration Resolution Algorithm for Mining Multiple Branches in Version Control Systems - Tarvo, Alexander; Zimmermann, Tom; Czerwonka, Jacek (Microsoft Research, 2010)
The high cost of software maintenance necessitates methods to improve the efficiency of the maintenance process. Such methods typically need a vast amount of knowledge about a system, which is often mined from software repositories. Collecting this data becomes a challenge if the system was developed using multiple code branches. In this paper, we present an integration resolution algorithm that facilitates data collection across multiple code branches. The algorithm tracks code integrations across different branches and associates code changes in the main development branch with corresponding changes in other branches. We provide evidence for the practical relevance of this algorithm during the development of the Windows Vista Service Pack 2.